2012
DOI: 10.5551/jat.12963
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Visceral Fat Correlates with the Decrease in the Number of Obesity-Related Cardiovascular Risk Factors in Japanese with Abdominal Obesity (VACATION-J Study)

Abstract: Aim: Visceral fat accumulation is associated with obesity-related cardiovascular risk factor accumulation and atherosclerosis. The present study investigated whether one-year reduction of the visceral fat area (VFA) correlates with a decrease in the number of such factors in Japanese with or without visceral fat accumulation. Methods: The study subjects comprised 5,347 Japanese, who underwent health check-ups in 2007 and 2008, including measurements of VFA and subcutaneous fat area (SFA) by computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 44 publications
(51 reference statements)
1
29
0
Order By: Relevance
“…The observed association between visceral obesity and preoperative metabolic comorbidities is consistent with previous studies that have linked cardiovascular risk factors to increased visceral fat 19 . Hiuge-Shimizu et al have reported that VFA and SFA were associated with obesity-related diabetes and hypertension whereas BMI was not 18, 19 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observed association between visceral obesity and preoperative metabolic comorbidities is consistent with previous studies that have linked cardiovascular risk factors to increased visceral fat 19 . Hiuge-Shimizu et al have reported that VFA and SFA were associated with obesity-related diabetes and hypertension whereas BMI was not 18, 19 .…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have utilized quantitative computed tomography (CT) to determine visceral obesity by measuring visceral fat area (VFA) 17 or visceral fat/subcutaneous fat area (V/S ratio) 18 and significant associations have been reported. A VFA of >100 cm 2 or V/S > 0.4 is associated with the metabolic syndrome 19 and poor surgical outcomes 6, 17 . Moreover, diagnostic CT adiposity measurements before colon cancer surgery, have yielded a significant association with short term complications such as wound complication, venous thrombosis and incisional hernia, compared to BMI 20, 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Even in mildly obese individuals, visceral adiposity is related to a cluster of risk factors and coronary artery disease (CAD) 6,7 . This pathogenetic condition, in which visceral fat accumulation locates upstream of various disorders related to CVD is conceptualized as visceral fat syndrome.…”
Section: Visceral Fat Syndromementioning
confidence: 99%
“…These cytokine changes induce insulin resistance and play a major role in the pathogenesis of endothelial dysfunction and the subsequent atherosclerosis. The rate of visceral fat accumulation is also different according to the gender and ethnic background, being more prominent in white men, African American women, and Asian Indian and Japanese men and women (Hiuge-Shimizu et al 2012). Such differences may explain the variation in the cardiometabolic risk between different populations.…”
Section: Introductionmentioning
confidence: 98%